1996
DOI: 10.1093/infdis/174.4.828
|View full text |Cite
|
Sign up to set email alerts
|

A Protective Domain of Heat-Shock Protein 60 from Histoplasma capsulatum

Abstract: Vaccination with recombinant (r) hsp60 protects mice against Histoplasma capsulatum. To map the domain of rhsp60 that confers protection, four gene segments were cloned into pET19b and expressed in Escherichia coli. rhsp60 fragments were tested for their capacity to induce proliferation by sensitized splenocytes and to protect BALB/c and C57BL/6 mice. All polypeptides stimulated cells from BALB/c mice immunized with yeasts or with rhsp60. Fragment 3 caused the most vigorous response by cells from mice immunize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 12 publications
1
38
0
Order By: Relevance
“…Subsequent studies revealed that a particular Ag within the extract, heat shock protein 60 (Hsp60), is immunogenic and confers protection against infection (7,8). Moreover, a region of Hsp60 between aa 172 and 443, termed fragment 3 (F3), is the protective domain of this protein (9). Studies have demonstrated Hsp60 to be a potent inducer of cellular immunity and an immunodominant Ag from Hc as well as other pathogenic organisms (10 -13).…”
Section: H Istoplasma Capsulatum (Hc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies revealed that a particular Ag within the extract, heat shock protein 60 (Hsp60), is immunogenic and confers protection against infection (7,8). Moreover, a region of Hsp60 between aa 172 and 443, termed fragment 3 (F3), is the protective domain of this protein (9). Studies have demonstrated Hsp60 to be a potent inducer of cellular immunity and an immunodominant Ag from Hc as well as other pathogenic organisms (10 -13).…”
Section: H Istoplasma Capsulatum (Hc)mentioning
confidence: 99%
“…Recombinant Hsp60 and F3 from Hc were generated as described previously (9). Briefly, genes expressing each protein were cloned in to the NdeI and BamHI sites of pET19b.…”
Section: Recombinant Hsp60 and F3 Productionmentioning
confidence: 99%
“…Using Concanavalin A three main glycoproteins of 84, 70 and 58 KDa were identified 17 , its sugar components bind collagen type II, fibronectin and laminin 18 . Other fungi have been shown to produce heat shock proteins (HSP) that could be locally responsible for the effects on the host immune system 12,24 .…”
mentioning
confidence: 99%
“…nfection with the pathogenic, soil-based fungus, Histoplasma capsulatum (Hc), 3 produces a wide spectrum of disease, ranging from a mild, influenza-like illness to a progressive, disseminated form that can be life-threatening if untreated. The extent of disease induced by Hc can be correlated to the number of fungal particles to which one is exposed.…”
mentioning
confidence: 99%